Sean Cotter, „Traducerea literară şi destinul României în comunism. Trei studii de caz: Blaga, Noica, Cioran”, translated and with a preface by Dana Bădulescu, Bucureşti: Humanitas, 2024, 248 p. - Mihaela MUDURE (Studia Universitatis Babeş-Bolyai. Philologia)
Sean Cotter, professor of literature and translation studies at the University of Texas at Dallas, is undoubtedly one of the most important international scholars interested in Romanian culture and literature. Dr Cotter is both a scholar with a solid background in comparative literature, proven by his Ph.D. at the University of Michigan, and a versed translator from Romanian. Up to now Dr Cotter gave excellent English equivalents to the works of important Romanian writers, such as Mateiu Caragiale, Nichita Stănescu, Magda Cârneci, or Mircea Cărtărescu. In 2014, Cotter published a monograph entitled Literary Translation and the Idea of Minor Romania at the University of Rochester Press.